A New Perspective on the Relationship between Trading Variables and Volatility in Futures Markets - Carchano, Oscar; Lucia, Julio; Pardo, Ãngel (International Journal of Economics and Financial Issues, 2017)
In this paper, we study the relationship between trading-related variables and volatility in futures markets, from a new unifying perspective, which is based on the separation of open and closed positions. Volatility in stock index futures markets (Standard & Poor’s 500, DAX 30 and Nikkei 225) is related to the flow of contracts entered into the markets and the flow of contracts that are closed out. In general, the daily changes in the number of open and closed positions are both positively correlated with volatility. Additionally, there is a stronger positive relationship between the number of open (respectively, closed) positions and contemporaneous volatility on those days when the opening of new positions (respectively, the closing of old ones) dominates the market. Finally, massive intra-day trading does not seem to alter the average volatility. The change in perspective allows us to provide a consistent story for the effect of the change in the open interest on the volatility analysed in the previous literature. Keywords: volatility; open interest; trading volume; open and closed positions. JEL Classifications: G12, G15